The development of a high-affinity conformation-sensitive antibody mimetic using a biocompatible copolymer carrier (iBody) - Blažková, Kristyna; Beranová, Jana; Hradilek, Martin; Kostka, Libor; Šubr, Vladimír; Etrych, Tomáš; Šácha, Pavel; Konvalinka, Jan (The Journal of biological chemistry, 2021)
Peptide display methods are a powerful tool for discovering new ligands of pharmacologically relevant targets. However, the selected ligands often suffer from low affinity. Using phage display, we identified a new bicyclic peptide binder of prostate-specific membrane antigen (PSMA), a metalloprotease frequently overexpressed in prostate cancer. We show that linking multiple copies of a selected low-affinity peptide to a biocompatible water-soluble N-(2-hydroxypropyl)methacrylamide copolymer carrier (iBody) improved binding of the conjugate by several orders of magnitude. Furthermore, using ELISA, enzyme kinetics, confocal microscopy, and other approaches, we demonstrate that the resulting iBody can distinguish between different conformations of the target protein. The possibility to develop stable, fully synthetic, conformation-selective antibody mimetics has potential applications for molecular recognition, diagnosis and treatment of many pathologies. This strategy could significantly contribute to more effective drug discovery and design.
Keywords: prostatický specifický antigen; nosiče léků; peptidová knihovna; Drug Carriers; Peptide Library; Prostate-Specific Antigen; lidé; biomimetické materiály; kalikreiny; Biomimetic Materials; Kallikreins; Humans